Application of Contemporary Theories of Learning in Educational Process - Zambrano, Kleyner Cristóbal Demera; Pazmiño Campuzano, Marcos Fernando (International Journal of Psychosocial Rehabilitation, 2020)
In educational settings in recent years, new educational concepts and approaches, pedagogical models, active methodologies and emerging educational trends have been discussed. Many of the promoters of these new paradigms propose to teachers at all levels to forget how they have learned and taught by adopting new educational tactics, to avoid falling into traditionalism due to the lack of use of techniques and strategies in current teaching, which allow a interactive, exciting and meaningful learning. The objective of this research is to analyze the application of contemporary theories such as: multiple intelligences, emotional intelligence, neurosciences, connectivism, constructivism, conceptual pedagogy, humanism and its incidence in the educational process; aimed at developing a comprehensive education for students that allows them to face the different challenges of the current knowledge society. The results obtained were achieved from a bibliographic review from an exploratory perspective, allowing to process key information from the study, the analysis-synthesis, inductive-deductive methods were considered, with information on the subject studied, obtaining as a result that these modern theories contribute to the improvement of the educational task, allowing the teacher to reorganize their curricular praxis, to provide a holistic education focused on the student, developing their capacities for the acquisition of new learning that will help them face the challenges of the globalized world.